Integration of CaCu3Ti4O12 capacitors into LTCC multilayer modules. Issue 11 (October 2015) - Löhnert, Romy; Capraro, Beate; Barth, Stefan; Bartsch, Heike; Müller, Jens; Töpfer, Jörg
Abstract The sintering behavior and electric properties of multilayer laminates made from tapes of CaCu3Ti4O12 (CCTO) with glass additive were studied. Sintering at 900 °C gives a fine-grained microstructure with a permittivity of ɛ′ = 900. The co-firing behavior of hetero-laminates of CCTO and commercial CT700 glass–ceramic LTCC tapes as well as with polycrystalline zinc titanate (ZT) LTCC tapes was studied. Co-firing of both hetero-laminates is possible, however, cracking due to shrinkage and thermal expansion mismatch was observed in the CCTO/CT700 combination. Co-fired CCTO/ZT multilayer laminates did not show any cracks, delaminations or other defects. CCTO multilayer capacitor elements were integrated into LTCC zinc titanate multilayer laminates and co-fired at 900 °C with AgPd electrodes.